The Early Sarmatian Elite Based on the Results of Archaeological and Anthropological Study of the Burials from a Kurgan Near the City of Volzhsky - Olga Shinkar; Mariya Balabanova; Evgeniy Pererva (Нижневолжский археологический вестник)
This article is devoted to the burial rite and anthropology of the early Sarmatian elite. The study is based on the data on the four burials from a single kurgan near the city of Volzhsky and the anthropological materials (skeleton remains of five individuals: 4 male and 1 child). An integrated approach was applied in the study which includes the archaeological and anthropological materials description using craniometry and cranioscopy and methods for describing the skeletons’ pathological conditions. For a more accurate diagnosis of pathologies, the X-ray method was applied. As a result of examining the burial rite and the material culture elements, the burials were dated back to the late 2nd – early 1st century BC. The features of the burial rite and the extraordinary material obtained as a result of excavations allow us to attribute the burials to the elite one. Morphological diversity of the skulls from these burials was revealed by their specific features, which classify them as belonging to the Caucasoid types with broad and narrow cranial vaults. The wide-headed complex presented by a skull from burial 4 is characterised by a very wide forehead and face with a flat horizontal profile. In addition, the presence of an unintentional occipital deformation is a specific morphological feature of this skull. The study of the pathological condition of the skeletons revealed traces of systematic physical overload and increased traumatisms. In addition, the skulls of the adult male individuals bear traces of changes in the type of vascular reaction, intracranial hypertension, etc. A possible wound to the 6th thoracic vertebra in a man from burial 2 can be attributed to a traumatic injury. A complete ankylosis of the 12th thoracic and 1st and 2nd lumbar vertebrae was revealed in a male from the same burial, which is a consequence of a compression fracture of the lumbar vertebra. Besides, a through wound of the frontal bone, most likely from an arrow or dart, was identified in a male from burial 4.